What do you do with an idea? - Yamada, Kobi.; Besom, Mae (Seattle, WA : Compendium, 2013)
"This is the story of one brilliant idea and the child who helps bring it into the world"--Dust jacket.
2.5
K-3
K-3
English
Keywords: Imagination -- Juvenile fiction; Imagination -- Fiction; Imagination -- Fiction